1988
DOI: 10.1099/0022-1317-69-7-1637
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Induction by Viruses. XVI. 2-Aminopurine Blocks Selectively and Reversibly an Early Stage in Interferon Induction

Abstract: SUMMARYA purine analogue, 2-aminopurine, reported to act as an inhibitor of protein kinase, selectively, reversibly and in a dose-dependent manner blocked a very early stage in interferon induction. With chick embryo cells and mouse L cells as hosts, and different viral inducers of interferon, maximal effects of 2-aminopurine were observed during the first 4 h of induction. At 10 mM-2-aminopurine there was a 20-fold reduction in the yield of interferon from both cell types. 2-Aminopurine and actinomycin D both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 33 publications
5
31
1
Order By: Relevance
“…2-Aminopurine has been shown to inhibit the doublestranded RNA-dependent protein kinase in vitro (21) and also blocks gene induction by double-stranded RNA (41,61,68). It is attractive to speculate that 2-aminopurine inhibition of gene induction by IFN-y and double-stranded RNA reflects the involvement of the same kinase in these two signal transduction pathways.…”
Section: -Aminopurine Selectively Blocks Gbp Induction By Ifn-ymentioning
confidence: 99%
See 1 more Smart Citation
“…2-Aminopurine has been shown to inhibit the doublestranded RNA-dependent protein kinase in vitro (21) and also blocks gene induction by double-stranded RNA (41,61,68). It is attractive to speculate that 2-aminopurine inhibition of gene induction by IFN-y and double-stranded RNA reflects the involvement of the same kinase in these two signal transduction pathways.…”
Section: -Aminopurine Selectively Blocks Gbp Induction By Ifn-ymentioning
confidence: 99%
“…In addition, similarities have been noted between the promoter elements conferring responsiveness to these agents (18,30,63). Recently, on the basis of inhibition by 2-aminopurine, three groups of investigators (41,61,68) have suggested that a kinase is involved in gene induction by double-stranded RNA. We tested the effect of 2-aminopurine on induction of GBP transcription by IFN-a and IFN--y (Fig.…”
Section: -Aminopurine Selectively Blocks Gbp Induction By Ifn-ymentioning
confidence: 99%
“…poly(rC) as an inducer (Cesario et al, 1988). A role for dsRNA-dependent protein kinase has been suggested in the induction of IFN-fl (Marcus & Sekellick, 1988;Zinn et al, 1988). Evidence for the latter, however, is based on the inhibition of IFN-fl induction by 2-aminopurine, without demonstration of a direct effect of the drug on dsRNA-dependent protein kinase or on cellular protein kinases.…”
Section: Introductionmentioning
confidence: 99%
“…Other consequences of virus infection or exposure to dsRNA are prevented by 2-AP, which may provide a clue to its mechanism of action. It prevents induction by virus or dsRNA of beta interferon, c-fos, c-myc, and tumor necrosis factor alpha by selectively blocking transcription of these genes rather than their translation (7,14,26,41,45). 2-AP may enhance gene expression at a translational level by inhibiting DAI kinase activated when plasmids are transfected into mammalian cells (17,19).…”
Section: Discussionmentioning
confidence: 99%